2005
DOI: 10.1007/s11165-005-0093-9
|View full text |Cite
|
Sign up to set email alerts
|

Student Perceptions of Chemistry Laboratory Learning Environments, Student–Teacher Interactions and Attitudes in Secondary School Gifted Education Classes in Singapore

Abstract: This study investigated the chemistry laboratory classroom environment, teacher-student interactions and student attitudes towards chemistry among 497 gifted and non-gifted secondary-school students in Singapore. The data were collected using the 35-item Chemistry Laboratory Environment Inventory (CLEI), the 48-item Questionnaire on Teacher Interaction (QTI) and the 30-item Questionnaire on Chemistry-Related Attitudes (QOCRA). Results supported the validity and reliability of the CLEI and QTI for this sample. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 26 publications
1
19
0
5
Order By: Relevance
“…Some articles interested in the quality or type of I/M/A suggested that learning in 'democratic' [199], 'self-accessed/paced/directed' [151], 'context-oriented' [75] and 'open-ended' [121] pedagogical settings was appreciated by highly performing students.…”
Section: School-related Variablesmentioning
confidence: 99%
“…Some articles interested in the quality or type of I/M/A suggested that learning in 'democratic' [199], 'self-accessed/paced/directed' [151], 'context-oriented' [75] and 'open-ended' [121] pedagogical settings was appreciated by highly performing students.…”
Section: School-related Variablesmentioning
confidence: 99%
“…A number of curriculum evaluation projects included student attitude to chemistry as one of the dependent variables (e.g., Adesoji and Raimi 2004;Thompson and Soyibo 2002), but they are not reviewed in this paper because they focused on the effectiveness of a curricular or instructional innovation rather than the attitudes of males and females toward chemistry lessons at different levels of schooling. Also, previous studies (e.g., Lang et al 2005) which merely used student attitude toward chemistry as a variable to correlate with other constructs are not included in this review. The findings of the nine previous studies are summarized below.…”
Section: Previous Researchmentioning
confidence: 99%
“…The seven scales are called Social Implications of Science, Normality of Scientists, Attitude to Scientific Inquiry, Adoption of Scientific Attitudes, Enjoyment of Science Lessons, Leisure Interest in Science, and Career Interest in Science. The TOSRA has been widely used in science education research (e.g., Joyce & Farenga, 1999;Lang, Wong, & Fraser, 2005;Smist, Archambault, & Owen, 1994;White & Richardson, 1993).…”
Section: Introductionmentioning
confidence: 99%